Facial asymmetry: a current review - Guilherme Thiesen; Bruno Frazão Gribel; Maria Perpétua Mota Freitas (Dental Press Editora, 2015)
Abstract The term "asymmetry" is used to make reference to dissimilarity between homologous elements, altering the balance between structures. Facial asymmetry is common in the overall population and is often presented subclinically. Nevertheless, on occasion, significant facial asymmetry results not only in functional, but also esthetic issues. Under these conditions, its etiology should be carefully investigated in order to achieve an adequate treatment plan. Facial asymmetry assessment comprises patient's first interview, extra- as well as intraoral clinical examination, and supplementary imaging examination. Subsequent asymmetry treatment depends on patient's age, the etiology of the condition and on the degree of disharmony, and might include from asymmetrical orthodontic mechanics to orthognathic surgery. Thus, the present study aims at addressing important aspects to be considered by the orthodontist reaching an accurate diagnosis and treatment plan of facial asymmetry, in addition to reporting treatment of some patients carriers of such challenging disharmony.